MANFAAT KAMPUNG KONSERVASI TUMBUHAN OBAT KELUARGA (TOGA) GUNUNG LEUTIK, DESA BENTENG CIAMPEA BOGOR - Rahila Juni Tanjungsari; Ervizal AM Zuhud; Ellyn K Damayanti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Conservation revitalization for health endurance can be achieved by establishing a conservation village such as Kampung Konservasi TOGA Gunung Leutik. The purposes of this research are to identify the benefit of Kampung Konservasi TOGA Gunung Leutik in the form medicinal plants utilization, and the impacts of its existence to local people’s health and economy. Methods used in this research was open-ended interview, and observation. The result shows that there are 152 medicinal plant species from 57 families that are utilized by the local people and most of them are from Zingiberaceae families. There are 40 recipe can be used for treat various desease. Benefits of these medicinal plants are for spices and daily disease treatment. The existence of Kampung Konservasi Gunung Leutik gives positive impacts for local people health and economy. Keyword: medicinal plant, TOGA conservation kampoong, utilization